Implementation of Flood and Drought Control for Economic Growth of the Cisadane River Flow in Banten - Risnawati, Risnawati; Irawati, Ira; Deliarnoor, Nandang A.; Nurasa, Heru (KnE Social Sciences, 2022)
The current growth of water conservation in Indonesia is still not optimally utilized by the community. The government has an important role in flood and drought disaster control to improve the welfare of its population. According to Indonesian Law No. 11 of 1974, water is a basic necessity for humans. However, human activities in agriculture, industry, and household activities can cause pollution, where the necessity for water increases yet its quality decreases. The water resource network in the watershed area of Banten Province, especially in Cisadane, is an old water resource facility and infrastructure, so there is some large and small scale damage, which certainly has an impact on the services to the water users. Related to flood control, the lake has a very important role as a water storage area and in reducing the amount of water runoff/water retention. The decline in the condition of the flow of rivers, lakes, reservoirs and swamps is inseparable from physical predicaments such as land conversion, and non-physical ones such as natural disasters. Therefore, the government’s role is important to provide information on flood and drought disaster control management systems so that the community can support their economic stability and be properly maintained. Keywords: implementation program, optimization, conservation of water resources, flood and drought disasters